The Hellenistic Mosaic Head from Dor, Israel: Reconsidered - Ovadiah, Asher (Gerión. Revista de Historia Antigua, 2013)
A unique mosaic fragment, found during the archaeological excavations at the site in 2000, dated to mid-late second century BCE, depicts a head among a garland, probably part of a decorative border for a central emblema. The aim of this article is to determine, on the basis of literary sources, iconographic and stylistic analyses, as well as comparative examples, whether the head does illustrate a mask or, alternatively, a depiction of the god Dionysos.
Keywords: Dionysos; Emblema; Enthousiasmos; Fillet; Garland; Mask; Protome. Tainia.